Uveitis attack and drug reaction due to cefuroxime axetil. (2nd July 2016) - Akman, Canan; Duran, Arif; Kalafat, Utku Murat; Ocak, Tarık
Abstract: Antibiotics are natural or synthetic substances that are used to control bacterial infections because antibiotics are by definition only effective against bacteria. A 30-year-old female came to our emergency clinic complaining rubor in both eyes, especially in the left eye, with swelling, rubor and pain in ears, and eruption in lips extremities. In her anamnesis, it has been determined that she did not have any medical disease that requires regular utilization of drugs. After the patient received cefuroxime axetil for acute tonsillitis, she observed eruptions in lip extremities on the 3rd day, but she did not care about it. On the 5th day, rubor in both eyes and, especially in the left eye, have been developed, and complaints such as unable to look toward light and pain have started together with swelling, rubor, and pain in both ears. She came to our clinic because she was very much worried about the situation. In this study, we aimed to discuss a drug reaction characterized by face and ear skin observations, due to uveitis after the use of antibiotics including cefuroxime axetil for acute tonsillitis.